Swimming pool at Steinbeck's Sag Harbor home - Unknown::::::::::::::: (Sag Harbor, New York)
View of the pool John Steinbeck had built for Elaine's 51st birthday (Aug.1965) in their yard in Sag Harbor, N.Y.